2002
DOI: 10.1177/108705470200500303
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Brown ADD Scales: An investigation in a predominantly inattentive ADHD adolescent sample with and without reading disabilities

Abstract: The Brown ADD Scale for Adolescents is widely used in clinical settings, yet, no published studies have investigated divergent and concurrent validity and specificity and sensitivity to inattentive ADHD symptomatology. Ninety-eight participants (13 to 16 years) were classified as ADHD/I and/or reading disabled (RD) using Kiddie Schedule for Affective Disorder and Schizophrenia (K-SADS), Conners' Rating Scales (CRS-R), and Ontario Child Health Study Scales (OCHSS), WRAT3, and WRMT-R. The results were: 29 ADHD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Moreover, we found that average real-time effort and retrospective effort differed significantly in the at-risk and non-risk groups even after controlling for task performance. These findings are consistent with the theoretical literature in suggesting that the experience of a cognitively demanding task may be especially uncomfortable and effortful for individuals who struggle with ADHD-related difficulties (Brown, 1996; Sergeant, 2000; Rucklidge and Tannock, 2002; Van Liefferinge et al, 2016). In summary, individuals at-risk for ADHD experienced the working memory task to require more effort and to be more uncomfortable, even after controlling for task performance; and they also found the experience of effort and discomfort to be more strongly correlated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, we found that average real-time effort and retrospective effort differed significantly in the at-risk and non-risk groups even after controlling for task performance. These findings are consistent with the theoretical literature in suggesting that the experience of a cognitively demanding task may be especially uncomfortable and effortful for individuals who struggle with ADHD-related difficulties (Brown, 1996; Sergeant, 2000; Rucklidge and Tannock, 2002; Van Liefferinge et al, 2016). In summary, individuals at-risk for ADHD experienced the working memory task to require more effort and to be more uncomfortable, even after controlling for task performance; and they also found the experience of effort and discomfort to be more strongly correlated.…”
Section: Discussionsupporting
confidence: 90%
“…It appears that the Effort Scale is assessing something akin to the ‘ how hard I (typically) try ’ aspect of mental effort given that items suggest a lack of energy and a failure to work to potential. Adolescents with ADHD have reported more difficulty sustaining effort as indicated by significant differences on the Effort Scale compared to an adolescent control group (Rucklidge and Tannock, 2002). Similarly, the Cognitive and Motivation in Everyday Life (CAMEL) Scale (Van Liefferinge et al, 2016), which assesses neuropsychological impairments in children and youth with ADHD, appears to tap into the ‘how hard I (typically) try’ aspect of mental effort.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the observed characteristics related to ADHD may be due to normative individual difference variables, such as cognitive or intellectual style (Zhang & Sternberg, 2005), or other clinical conditions (e.g., mood disorders; Cotrena, Branco, Shansis, & Fonseca, 2016;Rock, Roiser, Riedel, & Blackwell, 2014). However, the confluence of the particular set of characteristics assessed by the Brown ADD Scales has been suggested to be unique to ADHD (Rucklidge & Tannock, 2002).…”
Section: Relation To Previous Researchmentioning
confidence: 99%
“…ii) The BROWN ADD assessment scale includes a wider range of ADHD, not captured by the DSM-IV criteria. This scale includes 40 items assessing five clusters of ADHD-related executive function impairments and is especially useful in the assessment of the predominantly inattentive type of ADHD (14). There are cutoff scores and T-scores for subscales available for this instrument.…”
Section: Adhd Assessmentmentioning
confidence: 99%